2019
DOI: 10.1210/js.2019-sat-355
|View full text |Cite
|
Sign up to set email alerts
|

SAT-355 Comparison of Two Serum Cortisol Immunoassays versus Liquid Chromatography: Tandem Mass Spectrometry (LC-MS/MS)

Abstract: Accurate measurement of serum cortisol is required to diagnose and treat adrenal disorders. The most widely used methods in clinical laboratories for serum cortisol measurement are immunoassays which are offered in numerous commercial kits and on automated platforms. The LC-MS/MS is the gold-standard method to quantify serum steroids due its highest specificity, however it is a laborious methodology. Objective: to compare serum cortisol levels measured by two immunoassays versus LC-MS/MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…[ 17 18 19 ] Notably, the second-generation cortisol assays use monoclonal antibodies and are as specific as as liquid chromatography-tandem mass spectrometry (LC-MS/MS) with comparable cortisol levels measured by the two methods. [ 18 19 20 ] Such findings have not only been reported for Elecsys® Cortisol II in Cobas (Roche) and Architect Cortisol in i2000 Architect (Abbott) but also for Access Cortisol in Unicel DxI800 (Beckman Coulter), the assay used in our study. [ 16 17 19 ] Several recent studies have suggested lowering (12.6–15 μg/dL) the serum cortisol cut-offs in diagnosing AI with SST while using the second-generation cortisol assays to reduce its overdiagnosis.…”
Section: Discussionsupporting
confidence: 82%
“…[ 17 18 19 ] Notably, the second-generation cortisol assays use monoclonal antibodies and are as specific as as liquid chromatography-tandem mass spectrometry (LC-MS/MS) with comparable cortisol levels measured by the two methods. [ 18 19 20 ] Such findings have not only been reported for Elecsys® Cortisol II in Cobas (Roche) and Architect Cortisol in i2000 Architect (Abbott) but also for Access Cortisol in Unicel DxI800 (Beckman Coulter), the assay used in our study. [ 16 17 19 ] Several recent studies have suggested lowering (12.6–15 μg/dL) the serum cortisol cut-offs in diagnosing AI with SST while using the second-generation cortisol assays to reduce its overdiagnosis.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, in many institutions, this assay has been replaced with other more specific laboratory assays; liquid chromatography tandem mass spectrometry (LC/MS) or monoclonal antibody (mAb) immunoassay. Though cortisol immunoassays are widely used for their high performance and cost-effectiveness ( 4 ), LC/MS is considered the gold standard test ( 5 ). Previous reports suggest that these newer assays result in lower cortisol values than the traditional pAb immunoassay ( 6 ).…”
Section: Introductionmentioning
confidence: 99%